2014
DOI: 10.1103/physreve.89.042709
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking and cross-streamline migration of three-dimensional vesicles in an axial Poiseuille flow

Abstract: We analyze numerically the problem of spontaneous symmetry breaking and migration of a three-dimensional vesicle [a model for red blood cells (RBCs)] in axisymmetric Poiseuille flow. We explore the three relevant dimensionless parameters: (i) capillary number, Ca, measuring the ratio between the flow strength over the membrane bending mode, (ii) the ratio of viscosities of internal and external liquids, λ, and (iii) the reduced volume, ν=[V/(4/3)π]/(A/4π)3/2 (A and V are the area and volume of the vesicle). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 57 publications
9
36
0
Order By: Relevance
“…In 3D, a semi-axisymmetric croissant shape (as opposed to fully axisymmetric parachute shape; see Fig. 1) has also been observed in recent simulations by Farutin et al [8] in unconfined Poiseuille flow. That study reported a phase diagram similar to [5] for near spherical vesicles (ν ≥ 0.9) with viscosity contrast λ = 1.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In 3D, a semi-axisymmetric croissant shape (as opposed to fully axisymmetric parachute shape; see Fig. 1) has also been observed in recent simulations by Farutin et al [8] in unconfined Poiseuille flow. That study reported a phase diagram similar to [5] for near spherical vesicles (ν ≥ 0.9) with viscosity contrast λ = 1.…”
Section: Introductionsupporting
confidence: 75%
“…We use this study of unconfined flow with no viscosity contrast (i.e., λ = 1) as a validation of our code as these results have been reported in [8]. In the unconfined Poiseuille flow simulations for reduced volumes ν = 0.90 and 0.95, "slipper ", "croissant" and "parachute" shapes are observed as C a is increased.…”
Section: A Viscosity Contrast λ =mentioning
confidence: 79%
“…We show the steady state deformation in Figure 2 for Ca = 0.05, 0.3, 0.6. The steady state is nearly spherical for stiff capsules, whereas, by increasing the capillary number, it develops a frontrear asymmetry and displays first a bullet-like, and then a croissant-like shape [41,43,44]. We refer to the shape as "croissant" rather than "parachute" following the convention in [41,44] according to which a "parachute" shape is perfectly axisymmetric.…”
Section: Resultsmentioning
confidence: 99%
“…The steady state is nearly spherical for stiff capsules, whereas, by increasing the capillary number, it develops a frontrear asymmetry and displays first a bullet-like, and then a croissant-like shape [41,43,44]. We refer to the shape as "croissant" rather than "parachute" following the convention in [41,44] according to which a "parachute" shape is perfectly axisymmetric. This is not the case here since the capsule either sees the periodic boundary conditions in z and the walls in y or adapts to the duct square crosssection [43,45].…”
Section: Resultsmentioning
confidence: 99%
“…This initial position is chosen since, in pressure-driven flows, deformable objects, e.g., elastic beads, capsules, and cells, naturally migrate toward the channel centerline of axisymmetric channels [36][37][38][39][40][41]. Therefore, the inlet channel can be considered as the final part of a sufficiently long straight channel.…”
Section: Resultsmentioning
confidence: 99%